2022
DOI: 10.1021/acs.jpca.2c05060
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Products Study of the Atmospheric Degradation of trans-2-Hexenal with Cl Atoms

Abstract: The gas-phase reaction between trans -2-hexenal (T2H) and chlorine atoms (Cl) was studied using three complementary experimental setups at atmospheric pressure and room temperature. In this work, we studied the rate constant for the titled oxidation reaction as well as the formation of the gas-phase products and secondary organic aerosols (SOAs). The rate constant of the T2H + Cl reaction was determined using the relative method in a simulation chamber using proton-transfer reaction time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Initiation of the VOC oxidation process is primarily driven by the sunlight-derived OH radical but also via reactions involving other oxidants. Papers in this virtual special issue include studies of the initiation reactions of VOC species by OH, Cl, O 3 , , NO 3 , and HCO, as well as by direct photolysis . Chamber studies, in which the products of a VOC oxidation process are identified and quantified, are also prevalent; two studies quantify the formation of secondary organic aerosol (SOA) in the reaction of OH or NO 3 with monoterpenes, , while a combined experimental/theoretical study shows that methylmethanimine oxidation via the OH radical is unlikely to compete with atmospheric hydrolysis of this species .…”
mentioning
confidence: 99%
“…Initiation of the VOC oxidation process is primarily driven by the sunlight-derived OH radical but also via reactions involving other oxidants. Papers in this virtual special issue include studies of the initiation reactions of VOC species by OH, Cl, O 3 , , NO 3 , and HCO, as well as by direct photolysis . Chamber studies, in which the products of a VOC oxidation process are identified and quantified, are also prevalent; two studies quantify the formation of secondary organic aerosol (SOA) in the reaction of OH or NO 3 with monoterpenes, , while a combined experimental/theoretical study shows that methylmethanimine oxidation via the OH radical is unlikely to compete with atmospheric hydrolysis of this species .…”
mentioning
confidence: 99%